Pt and Ti Complexes Immobilized onto Mesoporous Silica Microspheres and Their Interaction with Molecules of Biological Interest. Issue 24 (26th June 2017) - del Hierro, Isabel; Pérez, Yolanda; Cruz, Paula; Juárez, Rafael
Abstract : Mesoporous silica microspheres (MSMs) have been functionalized with triazole and pendant hydroxy moieties by a postsynthetic procedure. The functionalities have been prepared by a very efficient azide/alkyne click reaction with propargyl alcohol to yield the corresponding 1, 2, 3‐triazole. The subsequent reaction with cisplatin and titanocene as metallic precursors produces platinum and titanium complexes tethered onto the silica surface. The synthesized materials have been fully characterized by dynamic recrystallization kinetics (DRX), FTIR, N2 adsorption/desorption techniques, TEM, diffuse reflectance (DR) UV/Vis and 13 C cross polarization/magic angle spinning (CP/MAS) NMR spectroscopy. In addition, the interaction of these materials with molecules of biological interest such as guanosine and bovine serum albumin has been studied by means of solid‐state voltammetry techniques. Drug‐release experiments in simulated body fluid show sustained release profiles for the platinum complexes. Abstract : Mesoporous silica microspheres (MSMs) have been functionalized with triazole and pendant hydroxy moieties. Their reaction with cisplatin and titanocene gives platinum and titanium complexes tethered onto the silica surface. Solid‐state voltammetry techniques have been used to elucidate the structure of the tethered complexes in aqueous media and their interaction with molecules of biological interest.